OS EFEITOS DA ALTERAÇÃO DE GÊNERO E FORÇAS ARMADAS BRASILEIRAS: NECESSIDADE DE ADEQUAÇÃO AO NÚCLEO AXIOLÓGICO CONSTITUCIONAL (Reflection and Critique Law Magazine, 2020)
Given the conceptual and classificatory evolution of transsexuality in the medical sciences and the development of the theme also in law, it remains to be observed what is the legal treatment conceived by the Brazilian Armed Forces to the military or their transgender dependents. Faced with the problem, it was investigated a hypothesis that considers any suspension motivated exclusively by transsexuality as invalid under the fundamental and objective rights of the 1988 Republican Constitution, regardless of the time when the change of gender was registered due to its declaratory nature, a fact that also impact on the benefit granted on the binary criterion (male and female) to dependents. The research had as theoretical reference the Constitution of the Republic of 1988, having been executed through the hypothetical-deductive method, primarily with bibliographic survey, articles, theses, dissertations, laws and court decisions. The hypothesis initially presented was confirmed.